Interactive effects of dietary protein/lipid level and oil source on growth, feed utilisation and nutrient and fatty acid digestibility of Atlantic salmon - Karalazos, Vasileios; Bendiksen, Eldar Asgard; Bell, J Gordon (Aquaculture, 2011)
Although the use of fish meal (FM) and fish oil (FO) has been extensive in Atlantic salmon culture, there is a growing need for less reliance on these commodities. Moreover, it is crucial for the aquafeed industry to optimise the use of dietary protein and to improve the protein utilisation in salmon diets. The interactive effects of the dietary protein/lipid level and rapeseed oil (RO) inclusion on growth, feed utilisation, nutrient and fatty acid (FA) digestibility and whole body chemical composition of large Atlantic salmon (Salmo salar L.), reared at summer water temperatures (11.6 °C), were investigated in a ten week feeding trial. The fish (initial weight 2053 g) were fed six isoenergetic diets in a factorial design containing 350 g kg−1/350 g, kg−1, 330 g kg−1/360 g kg−1, 290 g kg−1/380 g kg−1 of protein/lipid for high protein (HP), medium protein (MP) and low protein (LP) diets, respectively. At all protein/lipid levels the oil source was either FO or RO (60% of the added oil). At the end of the trial the final weights ranged from 3340–3664 g and the FCR from 0.99– 1.10. The protein level did not affect significantly any of the growth parameters but the oil source had a significant effect on final weight, specific growth rate (SGR) and thermal growth coefficient (TGC), showing improved growth with RO inclusion. This could be explained by the significantly higher lipid digestibility of the fish fed the diets containing RO (86.1 vs. 92.2%) which was probably affected by the diet FA composition; the apparent digestibility coefficient (ADC) of saturated FA, and to a lesser extent of unsaturated FA and especially monoenes, was improved by RO inclusion. The protein ADC was significantly affected by the protein level indicating a higher ADC for the HP diets compared to the LP (80.1 vs. 77.7%, respectively). Regarding the whole body composition, moisture was significantly affected by both factors, the fat content was significantly affected only by the oil source, while significant interactions were shown for the ...